2018
DOI: 10.1108/ijpdlm-06-2018-0231
|View full text |Cite
|
Sign up to set email alerts
|

Implications of product centric servitization for global distribution channels of manufacturing companies

Abstract: Purpose The ability to operate global distribution channels of products is commonly considered a critical determinant of a manufacturer’s competitiveness. Nowadays, many products are often complemented with value-added services challenging the efficacy of the status quo of distribution channels. Investigating this rather new phenomenon, the purpose of this paper is to provide an initial understanding of the implications of servitization for manufacturers’ global business-to-business (B2B) distribution. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…First, the study contributes to the emerging literature on global servitization by extending its focus to include the global service network perspective (Hakanen et al, 2017; Aminoff and Hakanen, 2018; Reim et al, 2019; Gölgeci et al, 2021). In particular, few studies have undertaken an in‐depth analysis of the dyadic transformation involved in providing advanced services (Kreye, 2017; Raddats et al, 2017; Töytäri et al, 2018; Kamalaldin et al, 2020; Sjödin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the study contributes to the emerging literature on global servitization by extending its focus to include the global service network perspective (Hakanen et al, 2017; Aminoff and Hakanen, 2018; Reim et al, 2019; Gölgeci et al, 2021). In particular, few studies have undertaken an in‐depth analysis of the dyadic transformation involved in providing advanced services (Kreye, 2017; Raddats et al, 2017; Töytäri et al, 2018; Kamalaldin et al, 2020; Sjödin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…First, servitization in global markets has received less research attention (cf. Hakanen et al, 2017;Aminoff and Hakanen, 2018;Gölgeci et al, 2021). Prior studies largely agree that successful servitization requires manufacturers to engage in open, joint action with partners to deliver advanced services to customers (Chesbrough, 2011;Randhawa et al, 2018;Visnjic et al, 2018;Kamalaldin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Building relational ties with multiple actors relate to integrating each actor's unique and critical capabilities for advanced service. Existing research have confirmed the positive role of strengthened relational ties in promoting business profitability and sustainability (Aminoff and Hakanen, 2018;Abreu et al, 2020). However, Windahl and Lakemond (2006) pointed out that the relationships can enable and obstruct the development of integrated solutions.…”
Section: Relationship Related Factorsmentioning
confidence: 99%
“…(2017);Wiesner and Thoben (2017);Aminoff and Hakanen (2018);Chakkol et al (2018);Vendrell-Herreroa et al (2018);Weigel and Hadwich (2018); Bustinza et al (2019); Parida et al (2019); Sjödin et al (2019); Abreu et al (2020); Yin et al (2020); Zhou et al (2020); Linde et al (2021); Access to complementary resources Improved effectiveness and efficiency of integrated solution development and delivery Decreased and costs and shared risks Strategic aspects Improved customer satisfaction Engaged in a longer-term relationship Created or enhanced sustainable competitive advantage Promotion of transformation towards sustainability Negative outcome Business aspects Increased additional costs Noori and Lee (2007); Lockett et al (2011); Jaakkola and Hakanen (2013); Chakkol et al (2014); Zhu and Zolkiewski (2015); Burton et al (2016); Lütjen et al (2017); Aminoff and Hakanen (2018); Töytäri et al (2018); Wang et al (2018); Hullova et al (2019); Reim et al (2019); Datta (2020); Korkeamäki and Kohtamäki (2020); Paiola et al (2021); Poeppelbuss et al (2021); Wagstaff et al (2021); Gölgeci et al (2021) Incurred opportunism and misalignments Strategic aspects Difficulty in controlling and coordinating the involvement of multiple actors Disruptions of the relationship between actors Constraints from the interdependence among multiple actors…”
mentioning
confidence: 99%
“…Therefore, how to connect with customers affects income, profitability, and value has become a factor for competition (Pantano, Priporas, & Dennis, 2018a;Szmigin, Canning, & Reppel, 2005;Thomas & Jadeja, 2021). Online retailing aims to achieve a growing relationship that involves more customer satisfaction and a demand for increased service volumes (Aminoff & Hakanen, 2018;Kosiba, Boateng, Okoe Amartey, Boakye, & Hinson, 2018;Richards, Hamilton, & Empen, 2016). On the other hand, innovation is associated with developing new services and products (Edvardsson et al, 2018).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%